Insider trading in Malaysia: initiatives to combat insider trading among the public listed companies / Nurul Nadia Rahmatullah Maricar - Rahmatullah Maricar, Nurul Nadia (2018)
Insider Trading in Malaysia is getting more serious day by day. Each day there will be new cases arise and handled by the Securities Commission Malaysia (SC). Thus this questions on the level of awareness on insider trading and what are the initiatives that could be taken to combat insider trading. This research adopts the suggestions given by William E. Donnelly, Paul M. Miller, Timothy P. Burke and Hope M. Jarkowski. All these journalist highlights that by having policy and procedures on insider trading, it could help to make employees aware on insider trading and in the same time could combat insider trading. They suggest four initiatives that could help to combat insider trading which in this research adopt as the independent variables. First is the employee training, second is surveillance of employee trading, third is the restricted and watch list and the last point is inter-departmental communications. This research studies on the Insider Trading in Malaysia: Initiatives to combat insider trading among the public listed companies. The main focus is on employees working under public listed companies in Malaysia. A set of questionnaire were distributed to 127 employees working under public listed companies. Based on the findings, there are positive relationship between the dependent variable and independent variables as to conclude that employee training, surveillance of employee trading, restricted and watch list and inter-departmental communications could help to combat insider trading. This study also further explain on the findings, discussion, limitation and future research for insider trading.